Ready access to densely substituted furans using Tsuji-Wacker type cyclization - Masal, Dattatraya P.; Choudhury, Rahul; Singh, Aman; Reddy, D. Srinivasa (Journal of Organic Chemistry, 2022)
A competent method for the construction of highly substituted furans catalyzed by Pd(II) and Cu(II) chloride has been developed. The method provides easy access to di-, tri-, and tetrasubstituted furans from corresponding diols with relatively mild conditions in a unified strategy. The developed method has been successfully tested with more than 25 substrates, which resulted in furans of multiple substitution patterns with up to 84% isolated yields.